CORRECTING FIEDEL, ONCE AGAIN: MONTE VERDE AND THE PEOPLING OF SOUTH AMERICA. Issue 4 (August 2022) - Dillehay, Tom D; Pino, Mario; Ocampo, Carlos; Adovasio, James; Collins, Michael B; Saavedra, Jose; Rossen, Jack; Pollock, David
ABSTRACT: Corrections are made to Stuart Fiedel's (2022) recent errors and misrepresentations related to the late Pleistocene sites of Monte Verde and Huaca Prieta and to South American Fishtail projectile points.